(untitled) (Nordic Journal of African Studies, 2004)
This study examines in detail the place of functional communication in self-help activities for sustainable development in Osun State, from the points of view of the major stakeholders in the development of the rural society, viz: the change agents, community leaders, members of the community, facilitators and other sundry officials connected to small and large scale self-help promotion in our communities. In other words, the study tries to find out what type of communication strategies can be employed for successful self-help promotion in our rural communities, and how these communication variables can be maximally used to ensure speedy development of our rural areas. The sample for the study consisted of 150 adults from each of the four selected local councils, making a total of 600 subjects, which are made up of the adult educators, community change agents and adult members of the communities. Random Sampling Method (RSM) was employed to select four local government areas from all the geographical zones in Osun State, which are then considered to be fair representatives of local councils in Osun State. Questionnaire and oral interview are the principal instruments of data collection. Three null hypotheses are raised for the study, and the major technique of analysis is the T-test statistical method. The data collected is thereafter subjected to a thorough analysis, after which the results are discussed in line with the hypotheses developed for the study. The study therefore concluded and firmly established through the results of the data analysis that, there is a significant difference between provision of qualitative information and literacy awareness and participation of adults in self-help projects in Osun State.